Manajemen Unit Produksi Radio FM 89,4 MHz di SMK Ma’arif 2 Gombong Kabupaten Kebumen: Manajemen Unit Produksi Radio - Muhamad Saludin (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to produce: (1) analysis of digital library management at SMA Negeri 1 Temon; (2) Analysis of the factors supporting and inhibiting digital library management in SMA Negeri 1 Temon; (3) Innovation in digital library management at SMA Negeri 1 Temon. This research is a descriptive study with a qualitative approach. The subjects of this study were the head of the librarian, librarian, and technology and information employees of SMA Negeri 1 Temon. Data collection methods used are interviews, observation and documentation studies. Test the validity of the data by triangulation of sources and methods. Data were analyzed descriptively qualitatively with Miles and Huberman's interactive analysis model. The results of the study showed that every element of management from the planning stage to the evaluation had been carried out well and some had not been carried out optimally. This is because there are several obstacles faced, namely (1) the equipment in organizing digital libraries is not adequate in terms of specifications, for example scanners that are still flat bad and the RAM capacity does not support the process of transferring media collections (2) the limited ability of library human resources in the context of digital libraries. , and (3) the lack of cooperation with publishers or other libraries in the procurement of digital collections. However, as for the supporting factors to accelerate digital library management, namely full support by the principal of SMA N 1 Temon and the high willingness of the head of the library for the implementation of a digital library. The innovation related to digital library management at SMA Negeri 1 Temon is to add a special menu to access the principal to carry out direct supervision functions.